Cardiovascular diseases and air pollution in Novi Sad, Serbia - Marija Jevtić; Nataša Dragić; Sanja Bijelović; Milka Popović (International Journal of Occupational Medicine and Environmental Health, 2014)
Objectives: A large body of evidence has documented that air pollutants have adverse effect on human health as well as on the environment. The aim of this study was to determine whether there was an association between outdoor concentrations of sulfur dioxide (SO2) and nitrogen dioxide (NO2) and a daily number of hospital admissions due to cardiovascular diseases (CVD) in Novi Sad, Serbia among patients aged above 18. Material and Methods: The investigation was carried out during over a 3-year period (from January 1, 2007 to December 31, 2009) in the area of Novi Sad. The number (N = 10 469) of daily CVD (ICD-10: I00-I99) hospital admissions was collected according to patients' addresses. Daily mean levels of NO2 and SO2, measured in the ambient air of Novi Sad via a network of fixed samplers, have been used to put forward outdoor air pollution. Associations between air pollutants and hospital admissions were firstly analyzed by the use of the linear regression in a single polluted model, and then trough a single and multi-polluted adjusted generalized linear Poisson model. Results: The single polluted model (without confounding factors) indicated that there was a linear increase in the number of hospital admissions due to CVD in relation to the linear increase in concentrations of SO2 (p = 0.015; 95% confidence interval (95% CI): 0.144-1.329, R2 = 0.005) and NO2 (p = 0.007; 95% CI: 0.214-1.361, R2 = 0.007). However, the single and multi-polluted adjusted models revealed that only NO2 was associated with the CVD (p = 0.016, relative risk (RR) = 1.049, 95% CI: 1.009-1.091 and p = 0.022, RR = 1.047, 95% CI: 1.007-1.089, respectively). Conclusions: This study shows a significant positive association between hospital admissions due to CVD and outdoor NO2 concentrations in the area of Novi Sad, Serbia.